Inner Derivations on Semiprime Gamma Rings - Chakraborty, Sujoy; Rashid, Md Mahbubur; Paul, Akhil Chandra (GANIT: Journal of Bangladesh Mathematical Society, 2019)
We study inner derivations and generalized inner derivations in semiprime Γ-rings to develop some important results. If f and g are inner derivations of a semiprime Γ-ring M satisfying the equation for all , then we show that . This equation produces a number of results on generalized inner derivations as well. GANIT J. Bangladesh Math. Soc.Vol. 39 (2019) 101-110